Framing the Information Security Process in Modern Society - Straub, D.; Goodman, S.; Baskerville, Richard (M E Sharpe Inc, 2008)
Describing the layout of the entire volume, this chapter explains how its parts emerged from an organic conception of organizations struggling to determine what their information security needs were and how to create viable security policies. Organizational issues exist within the context of both national and international developments in InfoSec and the final part deals with these critical arenas. Technological trends will dictate responses to the possibilities of security violations, and there are clear directions for such circumstances for such circumstances in the case of ubiquitous computing. The final chapter summarizes and reformulates the new directions that researchers should take in Info Sec.